Adherence to generic v. brand antidepressant treatment and the key role of health system factors. (February 2015) - Barbui, C.; Conti, V.
<x content-type="archive" xml:space="preserve">Abstract</x> One of the major challenges with antidepressant (AD) use is poor adherence and early treatment discontinuation. In addition to socio-demographic and clinical variables, treatment discontinuation may also be related to the capacity of the health system to assure and maintain continuity and intensity of care. Among health system factors that may interfere with adherence to pharmacological treatment, use of generic drugs may play a key role. It has been argued that, although the lower cost of generics may favour persistence on treatment, a widespread a priori scepticism about their effectiveness and safety by doctors and patients may have an opposite effect. This compelling research question has recently been addressed by an observational cohort study that involved 16 778 Medicare fee-for-service beneficiaries who received a new depression diagnosis and initiated generic v. brand AD therapy. The study found that generic initiation was associated with improved adherence. The benefits resulted from the lower out-of-pocket cost associated with generic ADs. In this commentary, we discuss the main findings of this study in view of its methodological strengths and limitations, and we suggest implications for policy.